FORMULATION AND OPTIMIZATION OF BIOACTIVE-LOADED POLYMERIC NANOPARTICLE – QUALITY BY DESIGN (QBD) STRATEGY EMPLOYING CENTRAL COMPOSITE DESIGN - MOHAMMAD GULSHAN; S. JOSHNA RANI (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: This study aimed to apply a quality by design (QbD) framework, utilizing central composite design (CCD), to systematically develop and optimize resveratrol-loaded polymeric nanoparticles. The overarching goal was to enhance the solubility, stability, and bioavailability of resveratrol, thereby improving its anti-depressant activity. Methods: Resveratrol nanoparticles were formulated using the solvent evaporation technique, incorporating poly(lactic-co-glycolic acid) (PLGA) as the biodegradable polymer and Poloxamer 188 as the stabilizing surfactant. High-shear homogenization was employed to ensure uniform particle formation. The nanoparticles were subsequently freeze-dried and characterized for key physicochemical parameters, including particle size, polydispersity index (PDI), zeta potential (ZP), encapsulation efficiency (EE), and in vitro drug release profile. Results: The CCD trial formulations containing PLGA and Poloxamer 188 at 60–80 mg and 2–3% concentration, respectively, exhibited particle sizes ranging from 236 to 461 nm with narrow size distribution (PDI: 0.15–0.22), and ZP values between −25 and −30 mV, indicating stable colloidal systems. EE varied from 60% to 90%, depending on the formulation variables. In vitro release studies demonstrated a prolonged drug release pattern, with approximately 97% of resveratrol released over a 48-h period. Based on the outcome of the optimization tool, PLGA and Poloxamer 188 were selected at a concentration of 63.56 mg and 2.20%, respectively, and the average particle size at 295.3±8.96 nm, PDI (0.19±0.01), EE (80.33±1.53), zetapotential (−27.00±1.00), and cumulative drug release was 99.33±1.15% for 48 h. Conclusion: The QbD-driven development approach enabled the successful formulation of resveratrol-loaded PLGA nanoparticles with enhanced physicochemical and release properties. This nanoformulation offers a promising strategy for improving the bioavailability and therapeutic efficacy of resveratrol, supporting its potential application in clinical settings.